KAINAN: Design and Implementation of a Gui-Based Python Restaurant Ordering and Billing System with SQLite Integration (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Efficient management of restaurant orders and billing is critical for providing quality service, minimizing errors, and improving operational workflow. Traditional manual billing systems are prone to inaccuracies, delays, and difficulty in tracking orders, particularly during peak hours. This study presents KAINAN, a GUI-based restaurant ordering and billing system developed using Python and integrated with an SQLite database. The system allows restaurant staff to create, view, update, and delete orders while automatically calculating bills and managing inventory. Object-Oriented Programming (OOP) principles ensure modularity, code reusability, and maintainability, while the graphical user interface (GUI) provides an intuitive and user-friendly environment. Functional testing confirmed that all modules, including order management, billing computation, and record updates, perform as expected. KAINAN improves accuracy, reduces human error, and streamlines restaurant operations, demonstrating the practical application of Python programming, GUI development, and database management in small to medium-scale food service establishments. Limitations include the absence of online payment integration and multi-user network functionality, which can be incorporated in future versions.